INOVASI PELAYANAN PUBLIK DI MASA PANDEMI COVID-19 DALAM MENINGKATKAN TATA PEMERINTAHAN DI KOTA CIMAHI - Sunasih Mulianingsih (PRODI ADMINISTRASI PEMERINTAHAN DAERAH FAKULTAS MANAJEMEN PEMERINTAHAN IPDN, 2021)
To improve Governance in Cimahi City during the Covid-19 pandemic, especially related to public services, it is necessary to have appropriate and fast public service innovations, so that public services continue to run well during the Covid-19 pandemic. Especially public services in the health sector, where The Cimahi City Health Office must carry out health service innovations for the people of Cimahi City quickly and precisely, so that the transmission of Covid-19 is well controlled, this study uses a qualitative descriptive method, with data sources obtained from print media, electronic media, and documentation. documentation and laws and regulations related to the handling of Covid-19. Conclusions/results that can be concluded that the Governance of the City of Cimahi, in handling the spread of the transmission of Covid-19, in Greater Bandung, (covering the City of Bandung, Cimahi City, Bandung Regency and West Regency ) is a very good one, because a The City of Cimahi in handling this health disaster, has used Digital Government Service, and the City of Cimahi is currently developing to make the City of Cimahi, a Smart City. And for the last 2 years Cimahi City has received an award from the Government, being a city that has succeeded in making innovations in public services, namely in 2019 and 2020. So public services during the pandemic are carried out with on-line-based applications. And only a few agencies that carry out public services directly, namely the Parks and Hygiene Service, the Fire Service and the Land Transportation Service, the rest use digital government service applications. Keywords: Public Service Innovation, Covid-19 Pandemic and Governance Government